638. Safety, Efficacy, and Durability of Long-Acting CAB and RPV as Maintenance Therapy for HIV-1 Infection: LATTE-2 Week 256 Results. (31st December 2020) - Smith, Graham; Henry, Keith; Podzamczer, Daniel; Masiá, Mar; Bettacchi, Christopher; Arasteh, Keikawus; Jaeger, Hans; Khuong-Josses, Marie-Aude; Sutton, Kenneth; Zhang, Feifan; McCoig, Cynthia C; Vandermeulen, Kati; et al.
Abstract: Background: Long-acting (LA) injectable suspensions of cabotegravir (CAB) & rilpivirine (RPV) are in phase III development. LATTE-2 W160 results demonstrated high rates of virologic response & overall tolerability. This W256 analysis evaluated long-term efficacy, safety, & tolerability of every 8-week (Q8W) & 4-week (Q4W) intramuscular (IM) dosing. Methods: LATTE-2 is a phase IIb, multicenter, parallel arm, open-label study in antiretroviral therapy–naive adults with HIV. After a 20-week Induction Period on oral CAB+abacavir/lamivudine, participants (pts) with plasma HIV-1 RNA< 50c/mL were randomized 2:2:1 to IM CAB LA+RPV LA Q8W, Q4W, or continue oral (PO) regimen in the Maintenance Period (MP). After W96, pts on IM regimens continued their current MP regimen. Pts randomized to PO in MP chose a Q8W or Q4W IM regimen in the Extension Period (EP). W256 analysis of MP & EP included virologic success with HIV-1 RNA< 50 c/mL (Food & Drug Administration Snapshot analysis), protocol-defined virologic failure (PDVF), & safety (intention-to-treat–Maintenance Exposed population). Results: At W256, 88% (101/115; Q8W) & 74% (85/115; Q4W) of randomized IM pts had HIV-1 RNA< 50 c/mL, as did 93% (41/44) of PO to IM pts. No pt developed PDVF after W48. In the randomized IM arm (MP & EP), excluding injection-site reactions (ISRs), nasopharyngitis (45%), diarrhea (28%), & headache (24%) were the most common adverse events (AEs), with 34% (39/115; Q8W) & 33% (38/115; Q4W) of pts reporting AEs ≥grade 3, of which 12% (14/115; Q8W) & 11% (13/115; Q4W) were drug related. 3% (3/115; Q8W) & 17% (20/115; Q4W) of pts had AEs leading to withdrawal. 22% (25/115; Q8W) & 23% (27/115; Q4W) reported serious AEs (3 were drug related). In the PO to IM arm (EP only), most common AEs excluding ISRs were nasopharyngitis (25%), influenza (23%), & back pain (18%). 23% (10/44) reported AEs ≥grade 3 & 5% (2/44) had AEs leading to withdrawal. Majority of ISRs were mild/moderate pain & discomfort. < 1% of ISRs were severe, with 5 pts discontinuing due to ISRs. Table 1 Table 2 Conclusion: CAB+RPV LA injectable therapy, administered Q8W or Q4W, demonstrated high rates of virologic response & tolerability through 5 years. W256 results add to previous results & demonstrate long-term durability of CAB+RPV LA for people living with HIV. Disclosures: Keith Henry, MD, Gilead (Research Grant or Support, Paid to institution)GSK/ViiV (Research Grant or Support, Paid to institution)Janssen (Research Grant or Support, Paid to institution)Merck (Research Grant or Support, Paid to institution) Daniel Podzamczer, MD, PhD, Gilead (Grant/Research Support, Advisor or Review Panel member)Janssen Pharmaceutica (Grant/Research Support, Advisor or Review Panel member)Merck Sharp & Dohme (Grant/Research Support, Advisor or Review Panel member)ViiV Healthcare (Grant/Research Support, Advisor or Review Panel member) Mar Masiá, MD, PhD, Janssen Pharmaceutica (Consultant, Other Financial or Material Support, Travel/accommodations/meeting expenses)Merck Sharp & Dohme (Consultant, Other Financial or Material Support, Travel/accommodations/meeting expenses)ViiV Healthcare (Consultant, Other Financial or Material Support, Travel/accommodations/meeting expenses) Hans Jaeger, MD, Abbvie (Consultant, Speaker's Bureau)Gilead Sciences (Consultant, Speaker's Bureau)Janssen (Consultant, Speaker's Bureau)MSD Sharp & Dohme (Consultant, Speaker's Bureau)ViiV Healthcare (Consultant, Research Grant or Support, Speaker's Bureau) Marie-Aude Khuong-Josses, MD, Viiv HC (Advisor or Review Panel member) Kenneth Sutton, MA, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Cynthia C. McCoig, MD, ViiV Healthcare (Employee) Kati Vandermeulen, MSC, Janssen Pharmaceutica (Employee, Shareholder) Rodica Van Solingen-Ristea, MD, Janssen R&D (Employee) William Spreen, PharmD, ViiV Healthcare (Employee, Shareholder) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee)